Corporate Citizenship: Toward an Extended Theoretical Conceptualization - Matten, Dirk; Crane, Andrew (Academy of Management Review, 2005)
We critically examine the content of contemporary understandings of corporate citizenship and locate them within the extant body of research dealing with business-society relations. Our main purpose is to realize a theoretically informed definition of corporate citizenship that is descriptively robust and conceptually distinct from existing concepts in the literature. Specifically, our extended perspective exposes the element of “citizenship” and conceptualizes corporate citizenship as the administration of a bundle of individual citizenship rights—social, civil, and political—conventionally granted and protected by governments.